MagneDyn the beamline for magneto dynamics studies at FERMI - Svetina, Cristian (Journal of synchrotron radiation, 2016)
The future Magneto Dynamics (MagneDyn) beamline will be devoted to study the electronic states and the local magnetic properties of excited and transient states of complex systems by means of the time-resolved X-ray absorption spectroscopy technique. The beamline will use FERMI's high-energy source covering the wavelength range from 60 nm down to 1.3 nm. An on-line photon energy spectrometer will allow spectra to be measured with high resolution while delivering most of the beam to the end-stations. Downstream the beam will be possibly split and delayed, by means of a delay line, and then focused with a set of active Kirkpatrick-Baez mirrors. These mirrors will be able to focus the radiation in one of the two MagneDyn experimental chambers: the electromagnet end-station and the resonant inelastic X-ray scattering end-station. After an introduction of the MagneDyn scientific case, the layout will be discussed showing the expected performances of the beamline